Improving Vietnamese Intellectual Property Law in the Context of Developing Artificial Intelligence - Que Anh, Nguyen Thi (VNU Journal of Science: Legal Studies; Vol 38 No 3, 2022)
The Fourth Industrial Revolution has had a strong impact not only on the natural sciences but also on the social sciences, including the legal sciences. The need to harmonize legislation and new technology requires analyzing the legal aspects of new technology as soon as possible and developing regulatory frameworks in a way that responds to development needs of new technologies. The article analyzes and evaluates the impacts of artificial intelligence technologies on the current legal-technical mechanisms for intellectual property rights protection in general and in Vietnam in particular, such as patent protection for algorithms in artificial intelligence, and copyright protection for objects created by artificial intelligence. Thereby, the author assesses the adaptation of Vietnam's current intellectual property law and makes recommendations to improve the law.